Influence of maternal and child factors on the dental service utilization among preschool children in Bangalore urban district: a cross-sectional study - S., Sruthy; Puranik, Manjunath P.; K. R., Sowmya (International Journal of Research in Medical Sciences, 2023)
Background: Dental visit is considered primary marker of oral care. Maternal characteristics, attitudes and psychosocial factors and the child’s oral health may influence dental visits of preschool children. This study aimed to determine the influence of maternal and child factors on dental services utilization among preschool children. Methods: A cross-sectional study was conducted among 600 preschool children and mothers visiting Anganwadis and Primary Health Centres in Bangalore Urban District. Mothers answered questions on socio-demographic characteristics and dental attendance. Maternal dental anxiety and child’s oral health-related quality of life were assessed using modified dental anxiety scale and early childhood oral health impact scale respectively. Oral health of children and mothers were assessed using WHO oral health assessment form 2013 for children and adults respectively. Descriptive statistics, Poisson’s regression with robust variance and mediation analysis were performed and p<0.05 was considered significant. Results: The proportion of dental visit among preschool children was 13.5%. Majority of the mothers had high dental anxiety (76.2%) and perceived their children’s oral health-related quality of life to be good (71.2%). The caries experience in mothers and children were 63.5% and 54.2% respectively. Mothers with higher education (PR=2.05, p=0.037), caries experience (PR=3.17, p<0.001) and poor perception of child’s oral health-related quality of life (PR=5.88, p<0.001), and children with pain experience (PR=1.62, p=0.003) and decayed teeth (PR=1.81, p=0.017) influenced children’s dental visit. Maternal perception on child’s oral health-related quality of life mediates the relationship between child’s oral health and dental visit. Conclusions: The utilization of dental services among preschool children was low. Maternal and child oral health factors influenced the child’s dental service utilization. Hence, oral health promotion approaches towards mothers and children is the need for the hour.